The Brazilian primary health care response to the COVID-19 pandemic: individual and collective approaches - Bousquat, Aylene; Giovanella, Ligia; Facchini, Luiz; Mendonça, Maria Helena Magalhaes; Nedel, Fulvio Borges; Cury, Geraldo; dos Santos Mota, Paulo Henrique; Schenkman, Simone; Chueiri, Patricia Sampaio; Alves, Maria Cecilia Goi Porto (Frontiers in Public Health, 2023)
Objectives Brazil’s PHC wide coverage has a potential role in the fight against COVID, especially in less developed regions. PHC should deal with COVID-19 treatment; health surveillance; continuity of care; and social support. This article aims to analyze PHC performance profiles during the pandemic, in these axes, comparing the five Brazilian macro-regions. Methods A cross-sectional survey study was carried out, using stratified probability sampling of PHC facilities (PHCF). A Composite Index was created, the Covid PHC Index (CPI). Factor analysis revealed that collective actions contrastingly behaved to individual actions. We verified differences in the distributions of CPI components between macro-regions and their associations with structural indicators. Results Nine hundred and seven PHCF participated in the survey. The CPI and its axes did not exceed 70, with the highest value in surveillance (70) and the lowest in social support (59). The Individual dimension scored higher in the South, whereas the Collective dimension scored higher in the Northeast region. PHCF with the highest CPI belong to municipalities with lower HDI, GDP per capita, population, number of hospitals, and ICU beds. Conclusion The observed profiles, individually and collectively-oriented, convey disputes on Brazilian health policies since 2016, and regional structural inequalities.